IDENTIFICATION OF WATER QUALITY IN THE MIDDLE CITARUM RIVER THROUGH PSYSICOCHEMICAL PARAMETERS DUE TO ANTHROPOGENIC ACTIVITIES (CASE STUDY: CITARUM RIVER SEGMEN IV) - Eka Sari, Navisya
Pollution of river water caused by anthropogenic pollutants is one of the issues that contributes to a deterioration in water quality and has an impact on aquatic ecosystems and water safety for consumption. The Middle Citarum River is a part of the Citarum River that connects to the Citarum reservoir cascades, which include the Saguling, Cirata, and Jatiluhur reservoirs. Pollution in the Middle Citarum River can harm its usage function as well as the reservoir's function because pollutants can collect in the reservoir and threaten its function. River water quality monitoring is essential for determining the condition of water bodies and the pollution that occurs in water bodies. The purpose of the study was to determine the impact of anthropogenic activities on water quality in the Middle Citarum River based on physicochemical parameters by collecting water samples using the composite sampling method at four sampling stations and analyzing them in the laboratory. The Pollutant Index, Storet, and CCMEWQI methods are used to determine water quality status. Agriculture, industry, settlements, fisheries, and hydropower plant are anthropogenic activities around the Middle Citarum River. These activities contaminated the Middle Citarum River, as evidenced by various physicochemical parameters that exceeded the quality standard such as COD, nitrites, oil and grease, detergent, total phosphate, and dissolved oxygen. Physicochemical parameters at all sampling stations, namely turbidity ranging from 8.75-94.50 NTU, TSS ranging from 6.50-38.50 mg/L, pH ranging from 6.66-8.50, dissolved oxygen ranging from 3.60-8.00 mg/L, total nitrogen ranging from 0.28-1.35 mg/L, nitrite ranging from 0.001-0.56 mg/L, nitrate ranging from 0.01-0.33 mg/L, ammonia ranging from 0.00-0.04 mg/L, total phosphate ranging from 0.29-3.90 mg/L, COD ranging from 6.47-37.07 mg/L, oil and grease ranging from 0.90-7.50 mg/L, and detergents ranging from 0.01-0.80 mg/L. The results of determining the water quality status of the Middle Citarum River based on Pollutant Index method indicated that the river was lightly polluted to moderately polluted, the Storet method indicated that the river was heavily polluted, and the CCME-WQI method indicated that the water body had a marginal class.